Multi-Scale Natural Fracture Prediction in Continental Shale Oil Reservoirs: A Case Study of the Fengcheng Formation in the Mahu Sag, Junggar Basin, China - Wang, Xiaojun; Jin, Zhijun; Chen, Gang; Peng, Miao; Huang, Liliang; Wang, Zhenlin; Zeng, Lianbo; Lu, Guoqing; Du, Xiaoyu; Liu, Guoping (Frontiers in Earth Science, 2022)
Natural fractures in continental shale oil reservoirs of the Fengcheng Formation in the Mahu Sag show multi-scale characteristics, which leads to complex seismic responses and difficult identification. In order to establish fracture prediction models with good performance in these reservoirs, this study uses seismic attributes such as post-stack coherence, curvature, likelihood, and pre-stack AVAz to predict the multi-scale fractures, including main-secondary faults, large-scale fractures, and medium-small scale fractures in continental shale oil reservoirs. The final prediction results are superimposed on the plane to clarify the multi-scale fracture distribution law of the Fengcheng Formation in the Mahu Sag. Seismic prediction results show that natural fractures in the upper sweet spot of the Fengcheng Formation are more developed, especially in the northern and central platform areas, and they are mainly near E-W strikes. With the increase of the primary-secondary fault distance, the fracture density gradually decreases. Natural fractures obtained by seismic prediction are consistent with the fractures interpreted by image logs, which can be used to effectively predict fractures for continental shale oil reservoirs in the Mahu Sag of the Junggar Basin and other areas with a similar geological background.